mr fantastic MHF Hall of Fame Dec 2007 16,948 6,768 Zeitgeist Mar 9, 2011 #2 homerb said: intergral of 3x/3x-2 dx Click to expand... Note that \(\displaystyle \displaystyle \frac{3x}{3x - 2} = \frac{(3x - 2) + 2}{3x - 2} = 1 + \frac{2}{3x - 2}\).
homerb said: intergral of 3x/3x-2 dx Click to expand... Note that \(\displaystyle \displaystyle \frac{3x}{3x - 2} = \frac{(3x - 2) + 2}{3x - 2} = 1 + \frac{2}{3x - 2}\).
BAdhi Oct 2010 252 76 Gampaha, Sri Lanka Mar 9, 2011 #3 \(\displaystyle \frac{3x}{3x-2}=1+\frac{2}{3x-2}\) now it's easy to integrate
H homerb Oct 2008 46 0 Mar 9, 2011 #4 So, after that do i do u= 3x-2 du= 3 dx? or what is the next step?
mr fantastic MHF Hall of Fame Dec 2007 16,948 6,768 Zeitgeist Mar 9, 2011 #5 homerb said: So, after that do i do u= 3x-2 du= 3 dx? [snip] Click to expand... Yes.
BAdhi Oct 2010 252 76 Gampaha, Sri Lanka Mar 9, 2011 #7 \(\displaystyle x+\frac{2}{3}ln|3x-2|+c\) NOTE: differentiate and you can check your answer for yourself Last edited: Mar 9, 2011
\(\displaystyle x+\frac{2}{3}ln|3x-2|+c\) NOTE: differentiate and you can check your answer for yourself